Internalization of Tasawuf Akhlaki (Ethical Sufism) Values in the Social Interactions of Vegetable Sellers at the Rabuan Market, Sumenep - Dini Salsabela; Ihwan Amalih (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
The dynamics of interaction among traditional traders are often characterized by fierce competition; traders are required not only to generate profit but also to uphold moral values ​​in their trade. In this context, tasawuf akhlaqi (Sufism focused on ethics and character) serves as a spiritual foundation that fosters and guides the cultivation of noble character within social life. This article aims to analyze the social interactions of vegetable traders at the Rabuan market through the lens of tasawuf akhlaqi. The study employs a religious studies methodology with a phenomenological approach as the conceptual framework to analyze how the values ​​of tasawuf akhlaqi are internalized within the traders' social interactions. Based on the methods, approaches, and theories utilized, this article presents analytical-descriptive data rather than merely narrative-descriptive data. The findings reveal that amidst intense competition, vegetable traders are able to maintain a balance between economic interests and spiritual principles in their trade; this is primarily due to the internalization of tasawuf akhlaqi values ​​in their personal lives—acquired through influences such as parents, teachers, and their surrounding environment—which subsequently shapes their social interactions. Thus, tasawuf akhlaqi acts as a spiritual foundation capable of regulating inner states regarding behavior and managing conflicts among traders.